The Role of Tax Management as a Moderator in the Effect of Tax Retention Rate and Good Corporate Governance on Earning Quality - Susilawati, Susilawati; Holiawati, Holiawati; Suripto, Suripto (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2024)
The industrial sector plays a very important role in people's lives, as it is the part of the economy that is responsible for the production of goods and services. The primary objective of this research is to empirically explore the dynamic between Tax Retention Rate and Good Corporate Governance concerning Earning Quality, while simultaneously investigating the potential moderating role of Tax Management. Meanwhile, Good Corporate Governance is a critical factor that can affect the integrity and transparency of the company in carrying out its operations. Earning Quality, as a measure of the quality of a company's earnings, is the main parameter in measuring the company's financial performance. The study's research design follows quantitative and associative methodologies. The research population encompasses companies within the industrial sector, as listed on the Indonesia Stock Exchange during the temporal span from 2017 to 2021. Employing a purposive sampling technique, a sample comprising 15 companies, leading to a dataset of 75 observed data points, was selected. To conduct the analysis and hypothesis testing, panel data regression analysis was employed, utilizing Eviews version 12 as the analytical tool. The outcomes of the T-test analyses are noteworthy, as they reveal that both the tax retention rate variable and the good corporate governance variable distinctly influence earning quality. However, the importance of tax management as a mediator in the correlation between tax retention rate and earning quality is insignificant. The findings of this study are expected to provide new insights for stakeholders, regulators, and business practitioners in optimizing tax management and maintaining the quality of corporate profits in the Indonesian capital market environment.